Investigation of the Effect of Teaching with Drama Activities on Students' Achievement in Social Studies Lesson and Permanence of Knowledge - Zengin, Erdal; Halim Ulaş, A. (Asya Publishing and Consultancy, 2022)
The purpose of this research is to examine the effect of drama activities on the achievements of primary school fourth grade students in Social Studies Lesson and the permanence of knowledge. For this purpose, exploratory sequential design, one of the mixed research methods, was used. The research was carried out in a primary school affiliated to the Elazig Provincial Directorate of National Education. In order to obtain quantitative data in the research, the "Social Studies Course Achievement Test" was applied to the students. In order to obtain the quantitative data of the research, the pretest-posttest control group design was used. In order to obtain qualitative data, the data for the secondary data source of the exploratory sequential design were obtained by taking the opinions of the experimental group students through a semi-structured interviewform as a result of the application. In the research, students' teaching Social Studies Lesson with drama method; As a result of the analyzes made, there was a significant difference in favor of the experimental group in the pre-test and post-test mean scores of the groups in the achievement mean scores of the Social Studies Course. In addition, there was a significant difference in favor of the experimental group in the mean scores of the measurement results for the permanence of the information in the Social Studies Course. However, the results obtained from the qualitative findings also overlap with the quantitative results. © 2022, Asya Publishing and Consultancy. All rights reserved.
Keywords: Drama method; Permanence; Primary school; Social studies lesson; Success